Utilization of patient-reported outcomes to assess adherence to relugolix when combined with stereotactic body radiation therapy for intermediate to high-risk prostate cancer - Kelly Gaudian; Min Jung Koh; Min Ji Koh; Ryan R. Collins; Shaine Eden; Zoya Zwart; Malika Danner; Alan Zwart; Mark Fallick; Deepak Kumar; Paul Leger; Nancy A. Dawson; et al. (Frontiers in Oncology)
IntroductionInjectable GnRH receptor agonists have been shown to improve cancer control when combined with radiotherapy (RT). Relugolix is an oral GnRH receptor antagonist that achieves rapid testosterone suppression. Non-adherence to oral medications due to poor social support or bothersome side effects may increase the risk of cancer recurrence. This prospective study sought to evaluate early testosterone suppression and relugolix drug adherence when combined with prostate stereotactic body radiation therapy (SBRT). Utilization of patient-reported outcomes (PROs) to assess oral medication adherence and guide intervention may improve the appropriate utilization of oral medications. This study focuses on the use of the Simplified Medication Adherence Questionnaire (SMAQ) as a tool to assess relugolix adherence.MethodsRelugolix was initiated at least 2 months prior to questionnaire administration. Adherence was assessed using the SMAQ. Total testosterone levels were obtained at the time of SMAQ administration. Castration was defined as serum testosterone ≤ 50 ng/dL. Poor drug adherence was delineated as failure to reach castration or non-adherence per the SMAQ (any non-adherence answer, missed > 2 doses in last week or since last visit). To compare the demographic and clinical characteristics of patients who adhered to treatment versus who did not, t-test, Wilcoxon rank sum test, Chi-square test, and Fisher’s exact test were used. A p-value < 0.05 determined statistical significance.ResultsBetween August 2021 and December 2023, 78 men were treated at Georgetown with relugolix and prostate SBRT per an institutional protocol. The median age was 72, and 41% of patients were non-white. Patients initiated relugolix at a median of 4 months prior to the SMAQ (2-19 months). 96% of patients achieved castration (≤ 50 ng/dL) at the time of the SMAQ. 96% of men reported always taking relugolix at the appropriate time. 1% discontinued medication due to bothersome side effects, 17% reported forgetting to take the medication, and 4% reported missing a dose during the weekend. 98% and 93% did not miss a dose more than 2 times in the last week and since the last visit, respectively. Overall patient-reported drug adherence was 75%. No patient demographic or clinical characteristic predicted non-adherence.DiscussionRelugolix allows for high rates of castration and drug adherence when combined with prostate SBRT. Monitoring drug adherence during treatment allows for prompt detection of non-adherence and timely intervention. Future studies should focus on how to optimally incorporate this questionnaire into patient management.